Improvement of cutting performance for thick stainless steel plates by step-like cutting speed increase in high-power fiber laser cutting. (July 2018) - Seon, Sangwoo; Shin, Jae Sung; Oh, Seong Yong; Park, Hyunmin; Chung, Chin-Man; Kim, Taek-Soo; Lee, Lim; Lee, Jonghwan
Highlights: Methods for improving the cutting performance of thick steel plates were evaluated. With a waiting time, the performance was slightly improved but very sensitive. With a step-like cutting speed increase, the performance was greatly improved. This work is expected to contribute in dismantling of nuclear facilities. Abstract: A study was conducted to improve the cutting performance of a 60-mm thick stainless steel plate using a 6-kW fiber laser. Two techniques for improving the initial cutting performance were evaluated by preheating the work piece with a waiting time and step-like cutting speed increase. Both techniques showed improved cutting results compared to constant speed cutting. Among them, the method with a step-like cutting speed increase showed the better result in terms of cutting performance. As a result, a 60-mm thick stainless steel plate was cut at a maximum cutting speed of 72 mm/min with a preheating cutting speed of 24 mm/min. In order to confirm the effect of preheating, an additional experiment was performed to measure the temperature variation during the cutting process. Through this experiment, preheating temperature conditions were found to allow the specimen to be cut. It is expected that the results of this work will contribute to improving the cutting performance of thick metal structures in various industrial fields, as well as the dismantling of nuclear facilities using lasers in the future.